2023
DOI: 10.3389/fneur.2023.1153193
|View full text |Cite
|
Sign up to set email alerts
|

Targeted metabolomics reveals serum changes of amino acids in mild to moderate ischemic stroke and stroke mimics

Abstract: BackgroundThe pathophysiological processes linked to an acute ischemic stroke (IS) can be reflected in the circulating metabolome. Amino acids (AAs) have been demonstrated to be one of the most significant metabolites that can undergo significant alteration after a stroke.MethodsWe sought to identify the potential biomarkers for the early detection of IS using an extensive targeted technique for reliable quantification of 27 different AAs based on ultra-performance liquid chromatography tandem mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Arginine and proline metabolism have been shown to be associated with axon regeneration, and arginine is a necessary raw material for axon regeneration ( 37 ). L-ornithine produced during its metabolism has recently been shown to be one of the biomarkers used for early detection of stroke ( 38 ). L-ornithine transcarbamylase deficiency leads to elevated ornithine levels, which in turn cause impaired urea cycling that can lead to stroke-like episodes ( 39 ), impaired mitochondrial function and reduced antioxidant capacity ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Arginine and proline metabolism have been shown to be associated with axon regeneration, and arginine is a necessary raw material for axon regeneration ( 37 ). L-ornithine produced during its metabolism has recently been shown to be one of the biomarkers used for early detection of stroke ( 38 ). L-ornithine transcarbamylase deficiency leads to elevated ornithine levels, which in turn cause impaired urea cycling that can lead to stroke-like episodes ( 39 ), impaired mitochondrial function and reduced antioxidant capacity ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, increased plasma Asn levels have been associated with the acute stage of ischaemic stroke but not the chronic stage [20]. Furthermore, targeted metabolomics studies using UPLC-MS/MS in 286 patients aged 63 to 65 years revealed increased serum Asn in mild to moderate ischaemic stroke [22]. Our results show an increase in Asn in elderly people from the LSR to HSR group and from the MSR to HSR group, suggesting that Asn increases before the stroke, and not immediately after the vascular event.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies on ischaemic stroke using NMR and LC-MS have detected increased levels of asparagine and formate after the occurrence of stroke [19][20][21][22][23]. Some authors have suggested the involvement of pathways related to oxidative stress, such as the homocysteine metabolism and the formation of reactive oxygen species [24,25].…”
Section: Introductionmentioning
confidence: 99%